Research activities in general medicine: a scoping survey by the Internal Medicine Society of Australia and New Zealand. Issue 9 (10th August 2022) - Aung, Ar K.; Pickles, Robert; Knight, Anne; Shannon, Leigh‐anne; Bowers, Andrew; Donnelly, Sinead; Johnson, Douglas F.; Scott, Ian A.; Potter, Elizabeth L.; ,
Abstract: Background: In developing an effective framework for a collaborative research network (RN) that supports members involved in research, the Internal Medicine Society of Australia and New Zealand (IMSANZ) required a better understanding of the current level of research activity and engagement by general physicians, and factors influencing such engagement. Aims: To explore the current research landscape amongst general physicians in Australia and Aotearoa New Zealand. Methods: A questionnaire exploring research participation, scope, research enablers and barriers was disseminated to IMSANZ members over a 3‐month period. Core functions of IMSANZ‐RN, research priorities, potential solutions to perceived barriers and required level of support were also evaluated. Results: A total of 82 members, mostly senior medical staff (74.4%), responded to the survey (11.8% response rate). More than 70% were involved in impactful research across multiple disciplines, encompassing a wide range of research themes and topics. However, there is limited support and resources available to conduct research, with most projects being self‐instigated and self‐funded. There is overwhelming support to increasing the profile of research in general medicine through the establishment of IMSANZ‐RN, whose principal purposes, as identified by respondents, are to foster collaboration, promote research, provide research education and training, and share information among general physicians. Quality improvement studies (56.1%) and clinical trials (41.5%) were also identified as priority research types. Conclusions: This study has profiled the constraints faced by general physicians in conducting high‐quality collaborative research and provides insights into what is needed to support greater research engagement, through development of a discipline‐specific clinical RN.